Sistem Informasi Evaluasi Pelayanan Publik Puskesmas Berbasis Website pada Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi - Hutami Laksmi Kastanti; Kodrat Iman Satoto; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Community Health Center or commonly called as Puskesmas is one of the health public services in Indonesia. Puskesmas managed by the local goverment, namely The District/City Health Department. Like the other public services, Puskesmas must always make improvements to the service to fulfill the needs of the people. The local goverment need to be supervised by the central government, so that the service improvement can run properly. The government department that does the monitoring is Public Services Division of Ministry of Administrative Reform and Bureaucratic Reform. Every year, Public Services Division of Ministry of Administrative Reform and Bureaucratic Reform evaluate all the public services in Indonesia, including Puskesmas. The Evaluation is still done manually, by bringing the officers of The District/City Health Department to each Puskesmas to survey, then the data is rechecked by The Province Health Department. Then, the data is sent to Public Services Division of Ministry of Administrative Reform and Bureaucratic Reform for analysis. Thus, the evaluation become less effective and less efficient. Based on the background, the research carried out by studying the literature, and data collection, and analysis of the Public Services Division of the Ministry of PAN RB, followed by the design and manufacture of the system. Then the system will be tested to determine whether the system has been running well without any problems according to user requirements. After the testing is done, the system can be implemented at the Ministry of Public Oelayanan Division PAN RB. Based on the background and the research, it’s known that the evaluation system need to become more effective and efficient, by making a web-based information system that is connected to the internet. The information system is built using PHP as the program language and PostgreSQL for the database, which named Puskesmas Public Services Evaluation Information System.